Perbandingan Kebisingan Pesawat berdasarkan Waktu Operasional Bandara (Studi Kasus: Bandara Halim Perdana Kusuma) - Syahputra, Bramantio Wijaya (Jurnal Teknologi Kedirgantaraan, 2022)
Halim Perdana Kusuma Airport is 12 km from the center of Jakarta, has an area of ​​about 170 hectares, located in East Jakarta, there are many settlements around the airport that receive noise from airport operations. This study was made to determine the comparison of noise received by the community based on airport operating time. The study began with the determination of 3 measurement locations, namely on Jl. Kampung Baru 1, Jl. Amd XII, and Jl. Main Radar based on coordinates using GPS. The next step is to prepare a Sound Level Meter measuring device by installing it at a height of ± 200 cm. Measurements are made when without aircraft activity and with aircraft activity, the results of which will be used to obtain Leq and DNL values. By using measurement and calculation methods that have been adopted from Kep. Men. LH No.48 of 1996, so that at 3 points of measurement locations, it was found that aircraft noise was quite influential on residents living in settlements around the airport, where at Location 1 when there were no active aircraft, the DNL value dropped by 14.9 dB. 2 of 4.3 dB, and Location 3 of 9.2 dB. The DNL value obtained from the measurement results for Location 1 was 69.5 dB, Location 2 was 76.5 dB, and Location 3 was 71.1 dB. So that the DNL value in residential areas around the airport has exceeded the quality standard regulated in Kep. Men. LH No.48 of 1996, that is 55 dB.